Data of knowledge towards Zika Virus infection in Sabah, Malaysia - Noor Ain Haron; Syed Sharizman Syed Abdul Rahim; Jaeyres Jani; Nur Athirah Yusof; Zarina Amin; Khoo, Hooi Yuen; Lee, Hai Yen; Khor, Chee Sieng; Kim Kee Tan; Mohd Rohaizat Hassan; Wong, Chin Mun; Hani Kartini Agustar; et al. (Elsevier Inc., 2021)
This dataset presents a cross-sectional survey and was con- ducted to assess the knowledge on Zika Virus infection among adults in Sabah. The data were collected from De- cember 2019 to February 2021, 274 adults living in forest fringe communities were interviewed by trained personnel and have completed the distributed questionnaires. SPSS ver- sion 27.0 was used to analyzed the data. These data could serve as auxiliary information and/or research data for other researchers in Sabah. It could also serve as guide or refer- ence data to other researchers outside Sabah who may be interested in carrying out similar research in other state.